Quantifying bicycle network connectivity in Lisbon using open data - Abad, Lorena (2018)
Abad, L., & van der Meer, L. (2018). Quantifying bicycle network connectivity in Lisbon using open data. Information (Switzerland), 9(11), 1-14. [287]. DOI: 10.3390/info9110287